THE DYNAMICS OF COPYRIGHT ROYALTY MANAGEMENT FOR SONGS/MUSIC, AND ITS IMPACT ON THE PROTECTION OF CREATIVE RIGHTS - Sitti Fatimah Maddusila; Andi Intan Purnamasari; Bambang Hermawan; Annisa Nurfaidah (Faculty of Law, Universitas Lampung, 2026)
Indonesia's copyright royalty management system has evolved through the establishment of Collective Management Organizations (LMKs) and the National Collective Management Organization (LMKN), which are responsible for collecting, administering, and distributing royalties to creators. Despite this institutional framework, significant deficiencies continue to undermine the protection of creators' economic rights. This study examines the adequacy of legal protection afforded by the current royalty distribution system and analyzes LMKN's legal responsibility for unclaimed royalties. Using normative legal research with statutory, conceptual, and comparative approaches, the study applies prescriptive legal analysis. The findings indicate that, although the Copyright Law and its implementing regulations govern royalty management, they do not provide sufficient legal certainty regarding timely, transparent, and proportionate royalty distribution based on actual use of copyrighted works. In addition, the absence of clear rules governing LMKN's responsibility for unclaimed royalties weakens legal protection for creators' economic rights. This study proposes reconstructing Indonesia's royalty governance framework by redefining LMKN as a fiduciary administrator responsible for the accurate, transparent, accountable, and timely distribution of royalties. It also recommends mandatory implementation of Music Recognition Technology (MRT) or digital fingerprinting at commercial venues to improve data accuracy and transparency. These reforms would strengthen legal certainty, promote fairness, and enhance the protection of creators' economic rights in Indonesia.